Effects of N-acetylcysteine on regeneration following partial hepatectomy in rats with nonalcoholic fatty liver disease - (:unkn) unknown (SPRINGER, 2009)
To investigate the effect of N-acetylcysteine on regeneration following partial hepatectomy in rats with nonalcoholic fatty liver disease (NAFLD). N-Acetylcysteine was given to seven rats with NAFLD (group 1); physiological saline was given to seven rats with NAFLD (group 2); and physiological saline was given to seven rats with a normal liver (group 3). We performed two-thirds hepatectomy in all rats and removed the remnant liver tissue 48 h later to measure the mitotic index (MI), proliferating cell nuclear antigen, glutathione (GSH), and malondialdehyde (MDA) levels. Mitotic index values were significantly higher in group 1 than in groups 2 and 3, and higher in group 3 than in group 2. Proliferating cell nuclear antigen values were significantly higher in group 1 than in group 2, but no significant difference was found in comparison with group 3. Glutathione values in group 1 were significantly higher than in group 2 and MDA values in group 1 were lower than in group 2. There was no significant difference between groups 1 and 3 in GSH and MDA values, in both the two-thirds hepatectomy and 48-h tissues. N-Acetylcysteine enhanced regeneration after partial hepatectomy in rats with NAFLD. We believe that it exerted this effect through its influence on oxidative stress.
Keywords: N-Acetylcysteine; Fatty liver; Liver regeneration; Oxidative stress; IMPROVEMENT; STEATOSIS; INJURY; GRAFT; DONOR